IDENTIFICATION OF FACTORS AFFECTING THE INSEMINATOR PERFORMANCE IN SUPPORTING THE SUCCESS OF ARTIFICIAL INSEMINATION AT THE UPSUS SIWAB PROGRAM IN BALI - I G., Suranjaya; Sarini, N. P.; Dewantari, M. (Majalah Ilmiah Peternakan; Vol 23 No 2 (2020): Vol. 23 No.2 (2020)DO - 10.24843/MIP.2020.v23.i02.p05, 2020)
The study was conducted by survey method with the aim to find out the factors that influence the performance of inseminator and the success of artificial insemination (AI) in an effort to support the Upsus Siwab program in Bali. Determination of respondents is done by purposive sampling of IB inseminators throughout Bali. Data obtained from interviews, notes from inseminators and information from relevant agencies. Data analysis was performed descriptively and multiple regression was followed by step-wise to identify the factors that had the most role. The results showed that inseminator performance was significantly affected (P <0.05) by factors of age (X1), education level (X2), number of families (X3), available time (X4), length of training (X5), long as an inseminator (X6), location distance (X7) and staffing status (X8). Through step-wise analysis, the number of animals that can be inseminated per period (Y1) is significantly affected by X4, X6 and X7 with the equation Y1 = 15.35 X4 + 16.65 X6 + 28.57 X7 - 142.36 (P <0.05) with R2 = 0.575. Service per conception (Y2) and conception rate (Y3) are significantly affected only by X6 with the respective equations Y2 = 1,273 + 0.088 X6 with R2 = 0.375 and Y3 = 44.49 + 0.885 X6 with R2 = 0.364, while calving rate (Y4) is influenced by X6 and X7 with the equation Y4 = 45.28 + 0.95X6 - 0.368X7 with R2 = 0.408. Of the several factors identified, it turns out that the long as an inseminator (X6) is the most important role in inseminator performance to support the success of AI in implementing the Upsus Siwab program in Bali.